Venous lactate, pH and partial pressure of carbon dioxide levels as prognostic indicators in 110 premature calves with respiratory distress syndrome. (24th June 2017) - Yildiz, R.; Aydogdu, U.; Guzelbektes, H.; Coskun, A.; Sen, I.
Abstract : Hyperlactatemia, hypercapnia, low pH and low oxygen saturation (SatO2 ) are commonly observed in premature calves. These clinical indicators are associated with increased mortality in preterm human newborns with respiratory distress syndrome (RDS). The aim of this study was to investigate the prognostic importance of venous pH, partial pressure of carbon dioxide (pCO2 ) and lactate level and which parameters are related with mortality in premature calves with RDS. All premature calves (52 male/58 female) were admitted to clinic within 12–24 hours after birth and blood samples were also taken into heparinised plastic syringes from the jugular vein within 30 minutes following admission. Diagnosis of RDS was made by both clinical signs and blood gas results. For the evaluation of independent samples, t test was used to compare the venous blood gas indicators of surviving and non‐surviving premature calves. Receiver operating characteristics curves were used to determine a cut‐off value in terms of lactate and pCO2 measurements among non‐surviving and surviving calves. Venous pH, pCO2, SatO2, base deficit, bicarbonate (HCO3 ) and lactate levels showed a significant variance between surviving and non‐surviving calves. Mean venous pH, pCO2, SatO2, lactate levels in non‐surviving premature calves was 7.05, 78.9 mm Hg, 16.1 per cent and 9.50 mmol/l, respectively. Mean pH, pCO2, SatO2 and lactate levels in surviving premature calves were 7.29, 56.3 mm Hg, 25.5 per cent and 5.1 mmol/l, respectively. The cut‐off values for lactate and pCO2 were 7.5 mmol/l and 63.5 mm Hg, respectively. In conclusion, the results of the study show that venous blood lactate and pCO2 have prognostic importance in premature calves with RDS.